Calculator Program for Determining Properties of Built-up or Composite Members - Gossett, Stephen R. (Engineering Journal, 1982)
The advent of programmable calculators has increased the productivity of structural engineers considerably. Presented herein is a calculator program (written for the Hewlett- Packard HP-41C, utilizing its unique alpha-numeric capability) which eliminates the time-consuming calculations involved in determining the section properties of (a) built-up steel members or (b) composite sections. The program requires 314 program lines and 24 storage registers for execution. This article presents a brief description of the program, a printout of the program listing (Fig. 1), and a flowchart (Fig. 2). It also includes appropriate examples utilizing the HP 82143A printer.